NSAID Analysis Using Chromatographic and Spectrophotometric Methods - Vina Awallina Diroh; Rio Gusraya Unaldi; Mutiara Wayu Puspasari; Muhammad Muzhil Aslam (Asian Journal of Analytical Chemistry, 2023)
The purpose of this review article to evaluate the content of Nonsteroidal anti-inflammatory drugs (NSAID) using chromatographic and spectrophotometric methods. This journal review uses seven analytical methods on NSAID , namely high performance liquid chromatography (HPLC), fourier transform infrared (FTIR), gas chromatography (GC), thin layer chromatography (TLC), and spectrophotometry methods. The outcomes of every method have been elaborated in this paper and all of them can be used to detect the NSAID compounds.